Patients' perceived tolerance of side effects in phase I cancer clinical trials: A qualitative study. (12th October 2016) - Brédart, A.; Bodson, S.; Le Tourneau, C.; Flahault, C.; Bonnetain, F.; Beaudeau, A.; Coquan, E.; Dolbeault, S.; Paoletti, X.
Abstract : This qualitative study aimed to explore cancer patients' perceived tolerance of side effects in phase I drug trials. Patients with solid tumours receiving molecularly targeted agents with/without chemotherapy were eligible for inclusion. In‐depth semi‐structured interviews were carried out with 17 patients with a median [range] age of 63 [41–72] years. Treatment was discontinued in seven patients. Verbatim transcripts of the audio‐taped interviews were analysed using a constructivist grounded theory approach. Four conceptual categories emerged from data analysis, labelled "suffering from side effects" comprising a range of symptoms, psychosocial or role disturbances; "striving to cope with side effects" reflecting psychological strategies for managing side effects; "hoping" reflecting expectations about treatment efficacy and relief from side effects; and "appraisal of care." Among patients remaining in the trial, treatment was currently perceived as fairly tolerable. For most respondents, whether still in a trial or not, treatment discontinuation could not be justified by the non‐tolerance of treatment side effects. These results question the adequacy of patient‐perceived tolerance reports to determine an optimal drug dose for phase II trials. Confronted with patients' hopes and inappropriate beliefs, communication is challenging in phase I trials and could benefit from facilitating psychosocial interventions.